Identification of the sources of spring barley resistance to leaf diseases and smut - N. V. Shishkin; T. G. Derova; E. S. Doroshenko; О. S. Kononenko (Зерновое хозяйство России)
Spring barley resistance to diseases can reduce yield losses and amount of the applied plant protection products, and, accordingly, the costs for its cultivation. One of the most important tasks and conditions of the breeding process is the expansion of the genetic diversity of sources of resistance to unfavorable environmental conditions and the development of the varieties that possess resistance to pathogens. On the territory of the Rostov region, the most harmful and economically significant diseases of spring barley are helminth-spore spots and stone smut. The purpose of the current study was to identify the spring barley varieties resistant to helminth-sporiosis and smut. There have been presented the 3-year results on assessment of the domestic and foreign spring barley varieties for resistance to leaf diseases and smut. There have been studied 117 domestic and foreign varieties. The immunological properties of the spring barley varieties were studied in a field infectious nursery. The seed infection with spores was carried out by the S. Dimitrov's method using a nutrient environment. Sowing of the inoculated seeds was carried out at the end of the optimal terms. The analysis was carried out according to the number of infected stems. The infectious nursery with helminth-sporiosis was set up according to the Methodological recommendations (2008). On the basis of the current study, according to the immunological assessment, the varieties were divided into different groups of resistance to the studied pathogens. The genotypes with high immunological resistance degree to the complex of pathogens are of the greatest breeding value. There have been identified the sources of resistance to two pathogens. These are the varieties ‘Ratnik', ‘Zernogradsky 73', ‘Azov', ‘Kumir', ‘Elf', ‘Tan 1', ‘Zernogradsky 35', ‘Vikont' (Russia), ‘Getman', ‘Odessa 22' (Ukraine), ‘Viking' (Sweden). The identified sources of spring barley resistance to smut and spot diseases have been recommended for use in breeding programs for immunity.